Heat flow measurements in the Jane Basin, a back-arc basin, northern Weddell Sea - Lawrence A. Lawver; Richard P. von Herzen; DELLA VEDOVA, BRUNO (1985)
New heat flow measurements were aquired onboard RRS Discovery, together with integrated geophysical measurements, as part of a BAS-WHOOI cooperative research program. Preliminary results are presented.